Sex bias in letters of recommendation and personal statements for otolaryngology residency. Issue 6 (3rd October 2022) - Berk, Garrett A.; Ho, Tiffany D.; Stack‐Pyle, Taylor J.; Zeatoun, Abdullah; Kong, Keonho A.; Chaskes, Mark B.; Thorp, Brian D.; Ebert, Charles S.; Senior, Brent A.; Kimple, Adam J.; DeMason, Christine E.
Abstract: Objective: Application for otolaryngology residency is highly competitive, with letters of recommendation (LORs) and applicant personal statements (PSs) representing important components of the application process. However, their inherently subjective nature predisposes them to potential implicit bias. Otolaryngology has historically been predominated by male physicians and while implicit sex bias has been demonstrated in LORs for application to residency of multiple specialties, data is limited for otolaryngology. Methods: LORs and PSs for all otolaryngology applicants to an academic medical center during the 2019–20 and 2020–21 cycles were abstracted. Quantitative analysis was performed using Linguistic Inquiry and Word Count 2015 (LIWC2015), a validated software application designed to analyze various emotional, cognitive, and structural components of written text. Results: LORs written for females were found to be written from a perspective of higher expertise and confidence while LORs written for males were associated with a more honest, personal, and disclosing tone. Moreover, LORs written for female applicants were found to reference achievement and "grindstone" terminology more than those written for men. No differences were observed in any word category between PSs written by male and female applicants. Conclusion: Minor linguistic differences exist in multiple domains between LORs written for male and female applicants for otolaryngology residency. These tended to favor female applicants, with their letters demonstrating higher clout, achievement, and grindstone scores. This trend was unexpected in this historically predominantly male specialty. While differences were statistically significant, the overall difference in an entire letter of recommendation is likely subtle. Level of Evidence: 3. Abstract : Implicit sex bias has been demonstrated in letters of recommendation for application to residency of multiple specialties; however, data is limited for otolaryngology. Letters of recommendation and personal statements for all otolaryngology applicants to an academic medical center during the 2019–20 and 2020–21 cycles were analyzed using Linguistic Inquiry and Word Count 2015, a validated software application designed to analyze various emotional, cognitive, and structural components of written text. Minor linguistic differences exist in multiple domains between LORs written for male and female applicants for otolaryngology residency.